2010
DOI: 10.1243/09544097jrrt318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Track Stiffness Distribution on Vehicle and Track Interactions in Track Transition

Abstract: A model for dynamic analysis of the vehicle-track-subgrade coupling system was developed by utilizing the finite-element method. Based on the model, new types of vehicle and track elements are presented and their associated stiffness matrix, mass matrix, and damping matrix are formulated. Computational software is coded with Matlab. As an application example, influences of four kinds of transition patterns - abrupt change, step-by-step change, linear change, as well as cosine change for track stiffness distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 4 publications
1
29
0
7
Order By: Relevance
“…Comparing the numerical results from this research with those that were reported by Lei and Zhang [12] and Koh et al [13] it is concluded that the results are comparable. Also, the responses of present study are in good agreement with the previous ones.…”
Section: Verification Of the Vechile-track Modelssupporting
confidence: 82%
See 3 more Smart Citations
“…Comparing the numerical results from this research with those that were reported by Lei and Zhang [12] and Koh et al [13] it is concluded that the results are comparable. Also, the responses of present study are in good agreement with the previous ones.…”
Section: Verification Of the Vechile-track Modelssupporting
confidence: 82%
“…In the next stage, a vehicle/track problem is simulated using finite element method. In this regard, the results of the developed computer code are verified by comparing with numerical results of Lei and Zhang [12] and Koh et al [13]. Finally, comprehensive sensitivity analyses are performed on the effectiveness of the various parameters on the track stiffness.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Li et al (2010) categorized the track main damages in transition zones in three categories: a) geometric disturbance of track, b) mud pumping and c) damages of track components. The numerical results of Lei and Zhang (2010) et al showed that the stiffness transition pattern of the track has a significant effect on the dynamic behavior of track and train, and that a gradual track stiffness transition can significantly decrease the wheel-rail interaction forces at the transition zone.…”
Section: Introductionmentioning
confidence: 99%